2016
DOI: 10.1063/1.4959583
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Theory of melt-memory in polymer crystallization

Abstract: Details of crystallization processes of a polymer at the crystallization temperature T c from its melt kept initially at the melt temperature T m depend profoundly on the nature of the initial melt state and often are accompanied by memory effects. This phenomenon is in contrast to small molecular systems where the supercooling (T 0 m − T c ), with T 0 m being the equilibrium melting temperature, and not (T m − T c ), determines the nature of crystallization. In addressing this five-decade old puzzle of melt-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 30 publications
2
76
0
Order By: Relevance
“…For the random copolymers studied here, it is expected that only the longest sequences from the initial crystallites remain clustered at the highest heterogeneous T melt . The long characteristic times increasing with T melt , or small changes observed with time, could be explained considering different metastable states at each heterogeneous T melt , for example as perceived by Muthukumar . This unusual slow kinetics has also been explained considering the system as a weakly phase segregated medium where both sequence segregation and diffusion play a role in the dynamics of cluster dissolution .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For the random copolymers studied here, it is expected that only the longest sequences from the initial crystallites remain clustered at the highest heterogeneous T melt . The long characteristic times increasing with T melt , or small changes observed with time, could be explained considering different metastable states at each heterogeneous T melt , for example as perceived by Muthukumar . This unusual slow kinetics has also been explained considering the system as a weakly phase segregated medium where both sequence segregation and diffusion play a role in the dynamics of cluster dissolution .…”
Section: Resultsmentioning
confidence: 96%
“…14 The experimental evidence is consistent with a kinetic nature of melt memory. 5,6,10,11,15,23,[29][30][31][32] Even when cooling from the same melting temperature, the increase of crystallization temperature depends on molecular weight, the initial level of crystallinity or on how the standard crystalline state is prepared. However, systematic studies of the effect of melt annealing on residual melt memory are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In the second heating cycle thermal or mechanical history of the sample should have been eradicated. However, it has been shown that a memory effect regarding crystallinity, mainly due to remaining small crystallites, can be observed for polymers even after melting [35][36][37]. Therefore, even after melting the polymer once, a lower Δc p for aligned samples as consequence of the stretching during electrospinning can be observed (see Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Although the polymer chains became mobile, the viscosity of melt was still very high and restructuring of the polymer chain conformation would have required a long time. The polymer however was cooled down before chain ordering due to the electrospinning process was completely eradicated (memory effect) [35][36][37]. A significant increase in crystallinity was observed after irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Different from the isotropic melt, the melt with residual order normally displays a large reduction in the time required for crystallization or increase the crystallization temperature during cooling. [3,4] These remnant ordered domains in the melt act as nucleation sites, [5] resulting in fast crystallization rates, because of a decrease in the free energy barrier for nucleation from entropic considerations. [6,7] Such behavior is widely understood as a result of "melting memory effect".…”
Section: Introductionmentioning
confidence: 99%